Upaya Peningkatan Kesadaran Masyarakat Melalui Sosialisasi Keselamatan Berlalu Lintas dan Tertib Parkir di Kabupaten Bombana - Ramsi, Ramsi; Firman, Andi; Salam, M.; PS, Marthen; Hado, Hado; Putra, Adris Ade; Soeparyanto, Try Sugiyarto; Arsyad, , La Ode Muhamad Nurrakhmad; Nasrul, Nasrul; Laode, Ringo Taufan; Satyadharma, Maudhy Satya (Jurnal Gema Ngabdi, 2025)
The development of transportation grow, thus affecting the motorized vehicles number, especially motorbikes. This has consequences, namely traffic accidents. This provides encouragement for many parties to continue to socialize community service activities in order to encourage increased awareness of drivers in orderly traffic and also orderly parking of vehicles. The implementation of this traffic safety and orderly parking socialization activity was carried out for four days (February 10-13, 2025) in Bombana Regency with 80 service users who received socialization in the form of brochures and flyers by the socialization team. The results of the socialization evaluation obtained through the distribution of questionnaires showed that there was an increase in understanding of service users by 55.4% after socialization event, which indicates the effectiveness of understanding the contents of the material in encouraging increased understanding and awareness in safe, comfortable, safe traffic and obeying traffic rules.